Catalyst powder capable of improving toughness of artificial diamond and preparation method of catalyst powder

By using catalyst powder composed of metal nickel, iron and nano zinc oxide in artificial diamond synthesis, the problem of impurities affecting diamond performance in the prior art is solved, the high toughness and thermal stability of diamond are achieved, and the overall quality of diamond is improved.

CN119869535AInactive Publication Date: 2025-04-25HUNAN TIME DIAMOND TECH CO LTD

Patent Information

Application Number
CN202510255652.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing artificial diamond synthesis technology, the impurities introduced by the catalyst affect the magnetism of the diamond, thereby reducing its strength and thermal stability, especially under high temperature conditions, the strength drops significantly.

Method used

Catalyst powder composed of metal nickel, metal iron and nano zinc oxide in extended protruding spherical shape in microscopic states is used to improve the SP3 hybrid conversion efficiency and thermodynamic potential difference of diamond through the optimization of the interpolation structure and bond angle of nano zinc oxide, thereby improving the impact toughness and thermal impact toughness of diamond.

Benefits of technology

It significantly improves the impact toughness and thermal impact toughness of artificial diamonds, reduces the formation of internal inclusions of diamonds, improves the gloss and color of diamonds, and promotes the output of high-grade diamonds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869535A_ABST
    Figure CN119869535A_ABST
Patent Text Reader

Abstract

The invention discloses catalyst powder capable of improving toughness of artificial diamond and a preparation method of the catalyst powder, and relates to the technical field of synthesis of artificial diamonds.The catalyst powder is composed of metal nickel, metal iron and nano-zinc oxide which is in an extending and protruding spherical shape in the microscopic state and forms powdery mixed metal powder, and the nano-zinc oxide is stacked in an inserted mode. The metal nickel and the metal iron are filled in an inserting and stacking gap; according to the catalyst powder, the quality of the diamond is improved in two different modes, the impact toughness and the heat impact toughness of the diamond are improved, the preparation method is simple in structure, no redundant component is added, doping of useless impurities is reduced, recycling is convenient, and the resource utilization rate is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial diamond synthesis, and in particular relates to a catalyst powder capable of improving the toughness of artificial diamond and a preparation method thereof. Background Art

[0002] Artificial diamond single crystals and extended diamond powders are increasingly used in the cutting, grinding and polishing of hard and brittle materials. At present, most domestic manufacturers are using (Fe70Ni 30 ) 40 G 60 Powder catalyst alloy is produced by a domestic six-sided top press to prepare artificial diamonds. The difference is the cylinder diameter of the press, the size of the top hammer, and the size of the synthetic block. The factors, laws and indicators that affect the mechanical properties of diamond are mainly diamond magnetism, impact toughness (TI), and thermal shock toughness (TTI). There is the following relationship between the magnetism of diamond and other properties: 1) The magnetism is linearly related to the impurity content. The more impurities, the stronger the magnetism of diamond, and vice versa. The impurities in diamond mainly come from the catalyst used in synthesis, and these catalysts are generally metals such as iron, cobalt, and nickel, which are all ferromagnetic substances. 2) Magnetism is related to strength (TI, TTI) and crystal form. The weaker the magnetism, the better the strength and crystal form. But the relationship between them is not a strict linear relationship. 3) Magnetism is also related to thermal stability. The strength of strongly magnetic diamond decreases by 60% after being roasted at 700℃, while the strength of weakly magnetic diamond begins to decrease when sintered at 1100℃. Because magnetism has an adverse effect on the performance of diamond, especially the strength decreases after being subjected to high temperature. Therefore, diamond products used for metal bond abrasives, especially stone saw blades and geological drill bits, need to be magnetically separated so that they can withstand the test of high-temperature sintering during manufacturing. Diamonds used in the manufacture of electroplated products also need to be magnetically separated, otherwise nickel nodules will appear on the coating, resulting in waste.

[0003] The reaction mechanism of catalytic synthesis of diamond generally includes the following in the prior art: (1) Atomic alignment bonding theory: Gou Qingquan believed that the atoms corresponding to the catalyst and graphite were aligned and bonded vertically, which caused the structure of carbon atoms to change from SP 2 π hybridization state is transformed into SP 3 The hybrid state causes graphite to transform from a layered structure to a diamond structure. This theory explains why the catalyst alloy chooses a face-centered structure and the atomic spacing is equal to or close to the diamond lattice constant, and clarifies that the catalyst can only promote but not change the carbon atomic structure.

[0004] (2) Flux theory: Shen Zhutong proposed that under the action of excess pressure, graphite and molten metal atoms interact to form SP 3The hybridized carbon atoms and atomic groups (diamond crystal unit) produce melt segregation and diamond growth, forming a metal film, and the subsequent diamond growth follows the general crystal growth law. Considering the catalyst during synthesis as a molten state, the influence of catalyst alloys with different structures on diamond nucleation, growth and distribution can be explained.

[0005] (3) Kinetic effect. Chen Qiwu believed that when diamond nucleates, it must be covered with a catalytic metal film as a result of the volume-pressure effect. When the carbon atom concentration on the surface of the nucleated diamond is higher than the equilibrium concentration in this state, the diamond grows. The main driving force for crystallization is the thermodynamic potential difference between diamond and liquid phase. The synthesis process is regarded as the process of cultivating crystals from the catalyst solution, which explains the driving force of nucleation and growth.

[0006] According to the research of the inventors, if it is necessary to make the structure of carbon atoms by SP 2 π hybridization state is transformed into SP 3 The easier the hybrid state is, the easier it is to trigger the material. During the research, it was found that the zinc oxide material with a bond angle of 109.5° is indeed more likely to undergo sp 3 Hybridization, this is because sp 3 The ideal bond angle for hybrid orbitals is 109.5°, which enables the four hybrid orbitals to be evenly distributed in space, forming a regular tetrahedral structure123. When the bond angle of a material is close to this value, its electron cloud distribution and orbital overlap are more conducive to sp 3 The formation of hybridization, while utilizing the plasticity and stability of nanomaterials, can further improve and enhance the thermodynamic potential difference during nucleation and growth. Therefore, a solution for a catalyst powder that can improve the toughness of artificial diamond is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a catalyst powder capable of improving the toughness of artificial diamond and a preparation method thereof. The catalyst powder improves the quality of diamond in two different ways and improves the impact toughness and thermal shock toughness of diamond. The preparation method has a simple structure, does not add any extra components, reduces the addition of useless impurities, is easy to recycle, and has a high resource utilization rate.

[0008] To achieve the above object, the present invention provides the following technical solutions: A catalyst powder capable of improving the toughness of artificial diamonds is composed of metal nickel, metal iron and nano zinc oxide in the form of extended protruding balls in a microscopic state. The powdered mixed metal powders are interleaved with each other, and the interleaved gaps are filled with the metal nickel and the metal iron.

[0009] As a preferred solution of the present invention, the composition comprises 32-35% of metallic nickel, 32-35% of nano zinc oxide, and the remainder of metallic iron, by mass percentage.

[0010] According to the catalyst powder mechanism in diamond synthesis, the key to diamond nucleation is that the structure of carbon atoms is composed of SP 2 π hybridization state is transformed into SP 3 Hybrid state, while the driving force of diamond nucleation and nucleation growth depends on the thermodynamic potential difference between diamond and metal liquid phase, so under the conditions of reducing the pressure and temperature of diamond synthesis based on catalyst powder, improving its SP 3 The hybridization conversion efficiency and the improvement of thermodynamic potential difference can further increase the number of diamond nucleation and growth rate, which is beneficial to improve the crystal form of diamond, reduce the formation of inclusions inside diamond, improve the gloss and color of diamond, and promote the output of high-grade diamond.

[0011] Based on the above mechanism, in the present invention, based on the existing iron-nickel based catalyst powder, nano zinc oxide particles are mixed and added inside to form alloy particles for diamond synthesis; the bond angle of zinc oxide is 108°, which is more likely to undergo SP 3 Hybridization, and at the same time, zinc oxide is prepared into nano zinc oxide in the form of extended protruding spheres in a microscopic state. Since nano zinc oxide has a number of protrusions, they are interlaced with each other during the mixing process, which can fully support metallic iron and metallic nickel. At the same time, after supporting metallic iron and metallic nickel, it develops into a lamellar structure with the sphere as the center and expanding outward. Therefore, compared with the spherical structure, its specific heat capacity is reduced, thereby increasing the thermodynamic potential difference between diamond and the metal liquid phase, thereby improving the quality of diamond in two different ways, and improving the impact toughness and thermal shock toughness of diamond.

[0012] At the same time, the nanoparticles used have a stable structure and a high recycling rate.

[0013] The present invention also provides a method for preparing a catalyst powder capable of improving the toughness of artificial diamond, using the above catalyst powder raw material, comprising the following steps: ①, preparing nano zinc oxide particles in the shape of extended convex spheres; ②, Melting metallic iron and metallic nickel separately in a smelting furnace into which inert gas is continuously introduced; ③, mixing the obtained liquid metal iron and liquid metal nickel, adding the nano zinc oxide particles obtained in step ①, heating to 1800-2000° C., to obtain an alloy solution; ④. After the alloy solution in step ③ is cooled to room temperature, it is washed with ethanol solution for 3 to 5 times, and then washed with deionized water for 3 to 5 times, and then placed in a drying oven for drying at 60°C; ⑤. Grind the dried alloy block into powder and collect it.

[0014] Among them, the use of ethanol solution for cleaning can fully clean the free oxygen ions in the alloy solution, thereby reducing the oxygen content in the catalyst powder, and also has the effect of improving the crystal quality of diamond.

[0015] As a preferred embodiment of the present invention, the preparation steps of step ① include: S1. Disperse it into 90 ml of ethylene glycol solution using zinc chloride tetrahydrate and stir magnetically for 30 min until a uniform solution is formed; S2. Add hexamethylenetetramine to the above uniform solution and stir evenly, transfer the mixed solution to a 100 ml stainless steel reactor, and place it in an oven at 160° C. for 6 hours; S3, after cooling to room temperature, collect the precipitate, wash it with deionized water and ethanol 5 times and collect it by centrifugation, and dry the collected precipitate at 60°C for 4h; S4. Finally, the dried precipitate is placed in a tubular furnace, heated at a rate of 1°C / min, and calcined at 300°C for 3h in a nitrogen atmosphere. After naturally cooling to room temperature, nano zinc oxide particles in the shape of extended protruding balls are obtained. S5. Based on the above steps, prepare nano zinc oxide particles of required mass.

[0016] As a preferred embodiment of the present invention, the molar mass ratio of zinc chloride tetrahydrate to hexamethylenetetramine is 1:2-3.

[0017] In summary, the beneficial technical effects of the present invention are as follows: the catalyst powder provided by the present invention improves the quality of diamond in two different ways, and improves the impact toughness and thermal shock toughness of diamond. Specifically, nano zinc oxide material is added to the iron-nickel alloy, and nano zinc oxide in the shape of an extended convex sphere is prepared. The bond angle of the material itself is close to 109.5°, which makes it easier to generate SP 3 Hybridization, and at the same time, zinc oxide is prepared into nano zinc oxide in the form of extended protruding spheres in a microscopic state. Since nano zinc oxide has a number of protrusions, they are interlaced with each other during the mixing process, which can fully support metallic iron and metallic nickel. At the same time, after supporting metallic iron and metallic nickel, it develops into a lamellar structure with the sphere as the center and expanding outward. Therefore, compared with the spherical structure, its specific heat capacity is reduced, thereby increasing the thermodynamic potential difference between diamond and the metal liquid phase. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification, but do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1This is a schematic diagram of a scanning electron microscope of nano zinc oxide, a catalyst powder that can improve the toughness of artificial diamonds in this embodiment. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The present invention provides a technical solution: a catalyst powder capable of improving the toughness of artificial diamond and a preparation method thereof.

[0022] In this embodiment, the catalyst powder is composed of metal nickel, metal iron and nano zinc oxide in the form of extended protruding spheres in a microscopic state. Figure 1 As shown, the mixed metal powder is in powder form, the nano zinc oxide is interleaved with each other, and the interleaving gaps are filled with the metal nickel and the metal iron.

[0023] Specifically, by mass percentage, it includes 32% of metallic nickel, 32% of nano zinc oxide, and the remainder is metallic iron.

[0024] The above-mentioned catalyst powder is prepared by the following steps: ①. Preparation of nano zinc oxide particles in the shape of extended convex spheres: S1. Disperse 0.8 g of zinc chloride tetrahydrate into 90 ml of ethylene glycol solution and stir magnetically for 30 min until a uniform solution is formed. S2. Add 1.5 g of hexamethylenetetramine to the above uniform solution and stir evenly. Transfer the mixed solution to a 100 ml stainless steel reactor and place it in an oven at 160° C. for 6 h. S3, after cooling to room temperature, collect the precipitate, wash it with deionized water and ethanol 5 times and collect it by centrifugation, and dry the collected precipitate at 60°C for 4h; S4. Finally, the dried precipitate is placed in a tubular furnace, heated at a rate of 1°C / min, and calcined at 300°C for 3h in a nitrogen atmosphere. After naturally cooling to room temperature, nano zinc oxide particles in the shape of extended protruding balls are obtained. S5. Based on the above steps, nano zinc oxide particles of required mass are prepared; ②, Melting metallic iron and metallic nickel separately in a smelting furnace into which inert gas is continuously introduced; ③, mixing the obtained liquid metal iron and liquid metal nickel, adding the nano zinc oxide particles obtained in step ①, and heating to 2000° C. to obtain an alloy solution; ④. After the alloy solution in step ③ is cooled to room temperature, it is washed with ethanol solution for 3 to 5 times, and then washed with deionized water for 3 to 5 times, and then placed in a drying oven for drying at 60°C; ⑤. Grind the dried alloy block into powder and collect it.

[0025] In this embodiment, the method of adding component materials in steps is beneficial to improving the mixing quality of the alloy liquid. First, metallic nickel in a molten state is added to metallic iron in a molten state, and the temperature is continuously raised to 2000°C during the adding process, and then nano zinc oxide particles are added. Coupled with reasonable pressure, temperature and time design, it can be ensured that the powdered granular catalyst powder has a high internal uniformity and a uniform particle size, and its particle size is controlled below 200 mesh.

[0026] The catalyst powder prepared in this embodiment was mixed with graphite at a mass ratio of 1:1.2 when used, and diamond was synthesized in a six-sided top press at 5.5 GPa and 1500° C. for 30 minutes.

[0027] The particle size of synthetic diamond produced by this application is 38 / 41. According to JB / T 10987-2010 "Determination Method of Impact Toughness of Superhard Abrasive Synthetic Diamond", the test is finally carried out. The TI of 38 / 41 particle size diamond is ≥89, and the TTI is ≥83. Its impact toughness and thermal shock toughness are greatly improved.

[0028] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0029] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A catalyst powder for improving the toughness of artificial diamond, characterized in that: The invention is composed of metal nickel, metal iron and nano zinc oxide in the form of extended protruding spheres in a microscopic state, and the mixed metal powder is in powder form. The nano zinc oxides are interleaved with each other, and the interleaved gaps are filled with the metal nickel and the metal iron.

2. The catalyst powder capable of improving the toughness of artificial diamond according to claim 1, characterized in that: The invention comprises 32-35% of metal nickel, 32-35% of nano zinc oxide and the balance of metal iron in terms of mass percentage.

3. A method for preparing a catalyst powder capable of improving the toughness of artificial diamond, using the catalyst powder raw material according to claims 1-2, characterized in that: The following steps are involved: ①, preparing nano zinc oxide particles in the shape of extended convex spheres; ②, Melting metallic iron and metallic nickel separately in a smelting furnace into which inert gas is continuously introduced; ③, mixing the obtained liquid metal iron and liquid metal nickel, adding the nano zinc oxide particles obtained in step ①, heating to 1800-2000° C., to obtain an alloy solution; ④. After the alloy solution in step ③ is cooled to room temperature, it is washed with ethanol solution for 3 to 5 times, and then washed with deionized water for 3 to 5 times, and then placed in a drying oven for drying at 60°C; ⑤. Grind the dried alloy block into powder and collect it.

4. The method for preparing a catalyst powder capable of improving the toughness of artificial diamond according to claim 3, characterized in that: The preparation steps of step ① include: S1. Disperse it into 90 ml of ethylene glycol solution using zinc chloride tetrahydrate and stir magnetically for 30 min until a uniform solution is formed; S2. Add hexamethylenetetramine to the above uniform solution and stir evenly, transfer the mixed solution to a 100 ml stainless steel reactor, and place it in an oven at 160° C. for 6 hours; S3, after cooling to room temperature, collect the precipitate, wash it with deionized water and ethanol 5 times and collect it by centrifugation, and dry the collected precipitate at 60°C for 4h; S4. Finally, the dried precipitate is placed in a tubular furnace, heated at a rate of 1°C / min, and calcined at 300°C for 3h in a nitrogen atmosphere. After naturally cooling to room temperature, nano zinc oxide particles in the shape of extended protruding balls are obtained. S5. Based on the above steps, prepare nano zinc oxide particles of required mass.

5. The method for preparing a catalyst powder capable of improving the toughness of artificial diamond according to claim 4, characterized in that: The molar mass ratio of the zinc chloride tetrahydrate to hexamethylenetetramine is 1:2-3.

Citation Information

Patent Citations

  • Novel catalyst used for synthesis of diamond

    CN103418311A

  • Preparation method for improving diamond grade by using catalyst

    CN107626261A

  • Composite structure cubic boron nitride spherical alloy powder and preparing method and application of composite structure cubic boron nitride spherical alloy powder

    CN107695342A

  • Water atomization catalyst powder as well as preparation method and application thereof

    CN114192150A

  • Ni-Fe based catalyst alloy without cobalt and manganese and production thereof

    CN1406665A

Cited By

  • Catalytic agent for synthesizing artificial diamond and preparation method thereof

    CN120479458A